Multipeak Wavelength Detection of Ultra-Short Fiber Bragg Grating Array Based on Arrayed Waveguide Gratings and Convex Optimization Algorithm - Zheng, Di; Yue, Zizheng; Zou, Xihua; Yan, Lianshan; Pan, Wei (Journal of lightwave technology, 2025)
Ultra-short fiber Bragg gratings (US-FBGs), due to their compact structure and high spatial resolution, have significant application potential in the field of high-density multiparameter sensing networks. Moreover, the demodulation technology with multi-peak detection and good generalization characteristics is the key to promoting US-FBGs into practical engineering applications. Different from the traditional methods, in this paper, the multi-channel characteristics of array waveguide grating (AWG) are first utilized to conduct multi-point spectral sampling of the US-FBG array, and then the spectral reconstruction and multi-peak demodulation are achieved with the aid of convex optimization algorithms and peak-tracing algorithms. The proposed method is validated by demodulating a US-FBG array that combines five US-FBG sensors. The spectral reconstruction and multi-peak demodulation performance of the proposed method were systematically investigated for US-FBG arrays with identical and different bandwidths, respectively. Experimental results indicate high-accuracy spectral reconstruction with an average spectral reconstruction error of 0.13, and multi-peak wavelength demodulation performance with an average wavelength demodulation root mean square error (RMSE) of 10.7 pm under different situations. The proposed demodulation method has great potential in achieving low cost, high performance and high integration.